Modeling of Technological Processes of Machine-Building and Repair Manufacture - Vladimir Karpichev; Konstantin Sergeev; Aleksandra Bolotina (Communications - Scientific letters of the University of Zilina, 2019)
The proposed methods of constructing models of technological processes (TP) of production, repair and technical maintenance of objects in machine buildings, such as railway rolling tock, serves as the basis for development of information, mathematical and methodological support of the CAD system TP.Applying of information technology to solve the problems of technological design has ecently received intensive development. The research results show the effectiveness of the optimization approach to solving technological problems. Automation of the design of technological processes, based on use of digital technologies allows reducing the time for introducing new technical means and technologies into production, increasing the efficiency of production, repair and maintenance of objects in machine buildings.